2018
DOI: 10.2337/db18-0204
|View full text |Cite
|
Sign up to set email alerts
|

Extending Remission and Reversing New-Onset Type 1 Diabetes by Targeted Ablation of Autoreactive T Cells

Abstract: Preserving endogenous insulin production is clinically advantageous and remains a vital unmet challenge in the treatment and reversal of type 1 diabetes. Although broad immunosuppression has had limited success in prolonging the so-called remission period, it comes at the cost of compromising beneficial immunity. Here, we used a novel strategy to specifically deplete the activated diabetogenic T cells that drive pathogenesis while preserving not only endogenous insulin production but also protective immunity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Indeed, our analysis of CD4 + T-cell subsets showed that IFN-g + T cells represent the majority of CD4 + Teff cells. Published data support a pathogenic role for Teff cells in T1D, and ablation of Teff cells could significantly preserve b-cell function (29). Importantly, T1D patients receiving islet or pancreas allografts still had an association with autoimmunity recurrence years after disease onset, indicating the possibility of long-lasting autoimmunity of pathogenic T cells in autoimmune diabetes (30).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, our analysis of CD4 + T-cell subsets showed that IFN-g + T cells represent the majority of CD4 + Teff cells. Published data support a pathogenic role for Teff cells in T1D, and ablation of Teff cells could significantly preserve b-cell function (29). Importantly, T1D patients receiving islet or pancreas allografts still had an association with autoimmunity recurrence years after disease onset, indicating the possibility of long-lasting autoimmunity of pathogenic T cells in autoimmune diabetes (30).…”
Section: Discussionmentioning
confidence: 96%
“…Theoretically, activated, but not naïve, Teff cells drive diabetes pathogenesis ( 28 ). Selective depletion of Teff cells prolonged disease remission and preserved islet function in NOD mice ( 29 ). Moreover, memory T cells could be a reserve force to damage β cells in the relapse of autoimmunity.…”
Section: Introductionmentioning
confidence: 99%